An electrode of the second kind for aspirin determination in tablet formulations - Ferreira, VJF; Cavalheiro, ACV; Fagnani, E.; de Moraes, M.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP]; Melios, C. B. (Japan Soc Analytical Chemistry, 1999)
This paper describes the construction of an electrode of the second kind, Pt\Hg\Hg-2(Salic)(2)\Graphite, sensitive to salicylate. This electrode responds to the salicylate ion with a sensivity of 58.66 mV/decade over the range 6.0x10(-4) - 1.0x10(-1) mol/l at pH 6.0 and an ionic strength of 0.500 - 3.00 mol/l, adjusted with NaClO4. The electrode is easily constructed, shows a fast response time, is low in cost, has excellent response stability, and has a lifetime greater than 18 months, which is much longer than those reported earlier for other systems. The influence of 10 different carboxylate and inorganic anions on the electrode response showed that there was negligible interference by most of these ions. It was used to determine aspirin in tablets (after hydrolysis of acetylsalicylic acid to salicylate) by means of the standard additions method. The results obtained using this electrode for aspirin determination, in three different samples of antithermic drugs, compared favorably with the results given by the British Pharmacopoeia method.
Keywords: salicylate sensitive electrode; mercury-mercurous salicylate; pharmaceutical analysis; salicylate and acetylsalicylic acid determination